Efficiency of conventional versus Islamic banks: international evidence using the stochastic frontier approach (SFA) - Ramadilli Mohd, Shamsher Mohamad; Hassan, Taufiq; Bader, Mohammed Khaled I. (Islamic Bank Training and Research Academy, Islamic Bank Bangladesh Limited, 2008)
This paper measures and compares the cost and profit efficiency of 80 banks in 21 of Organisation of Islamic Conference (OIC) countries: comprising of 37 conventional banks and 43 Islamic banks, using the Stochastic Frontier Approach (SFA). In addition, it assesses the efficiency of those banks based on their size, age, and region. The findings suggest that there are no significant differences between the overall efficiency results of conventional versus Islamic banks. However, there is substantial room for improvement in cost minimisation and profit maximisation in both banking systems. Furthermore, the findings show no significance difference in average efficiency scores between big versus small and new versus old banks in both banking streams. This implies that size and age did not affect the performance of banks in both streams. Overall, the results are in favour of the more recent Islamic banking system.